Different effects of continuous-cover and rotation forest management on soil organic carbon stabilization in a boreal Norway spruce forest - Roth, Eva-Maria; Sietiö, Outi-Maaria; Adamczyk, Bartosz; Xu, Pingping; Valkonen, Sauli; Tuittila, Eeva-Stiina; Helmisaari, Heljä-Sisko; Karhu, Kristiina (Elsevier, 2026)
Clear-cut-based rotation forest management (RFM) is the dominant silvicultural system in boreal forests. Continuous-cover forestry (CCF), an emerging alternative, operates without clear-cutting. How these silvicultural regimes affect long-term SOC storage and quality remains unclear. This field study examined the effects of CCF and RFM on SOC quantity and stabilization in spruce-dominated forests in central Finland. We sampled (1) recently clear-cut plots, (2) even-aged mature plots (both representing RFM stages), (3) uneven-aged CCF plots, and (4) uncut controls. We analysed SOC stocks, root biomass, condensed tannins (root metabolites) and soil fungal necromass. SOC recalcitrance and accessibility for decomposition were assessed through chemical and physical fractionation and laboratory incubation. 13C and 15N abundances indicated the decomposition stage of soil organic matter (SOM) and contribution of mycorrhizal residues. Uncut forests had marginally higher root biomass than clear-cut and even-aged forests, while uneven-aged forests fell in between. Tannin concentrations were decreased in clear-cut plots. Fungal necromass correlated strongly with SOC but was unaffected by forest management. Contrastingly, greater 15N enrichment in CCF plots suggested higher impact of mycorrhizae in SOM formation. Although soil respiration rate in uncut plots was higher than in managed plots, chemical and physical fractionation analyses showed no treatment effects. While we did not find differences in total SOC stocks between treatments, our results revealed long-term management impacts on SOC quality and stabilization processes, as mycorrhizal fungi appeared to be more involved in SOM formation in uneven-aged plots. This may indicate a greater potential for long-term accumulation of stable SOM.
Keywords: soil organic carbon; amino sugars; fungal necromass; MAOC; POC; roots; natural abundance of stable isotopes